Sebuah Analisis Pelanggaran Maksim dalam Percakapan pada Pesan Whatsapp - Widya Eka Septiani (JournEEL, 2021)
The focus of this research is flouting maxim which is used by conversation on whatsapp message between Widya Eka Septiani and Edo Meggi Fernando as the students of English Education Study Program 2016. This research aims at: (1) describing the kinds of maxims flouted by conversation on whatsapp message between Widya Eka Septiani and Edo Meggi Fernando as the students of English Education Study Program 2016 and (2) revealing the reasons of flouting maxim showed by conversation on whatsapp message between Widya Eka Septiani and Edo Meggi Fernando as English Education’16. The research design of this study was descriptive qualitative research. The results of the research show that (1) the flouting maxims in conversation between Widya Eka Septiani and Edo Meggi Fernando by whatsapp message is flouting maxim of relation, and (2) revealing the reasons of flouting maxim showed by by conversation on whatsapp message between Widya Eka Septiani and Edo Meggi Fernando.